Fabrication of cellulose nanocrystals as potential anticancer drug delivery systems for colorectal cancer treatment - Mostafa, Yusefi; Soon, Michiele Lee Kiun *; Teow, Sin Yeang *; Monchouguy, Elaine Irene; Bibi Morheen, Haleema Mooneerah Neerooa; Zahra, Izadiyan; Jahangirian, Hossein; Rafiee-Moghaddam, Roshanak; Webster, Thomas J.; Kamyar, Shameli (Elsevier, 2022)
Polysaccharide nanocrystals have great potential to be used as improved drug carriers due to their low cost, high biodegradability, and biocompatibility. This study reports the synthesis of cellulose nanocrystals (CNC) loaded with 5-fluorouracil (CNC/5FU) to evaluate their anticancer activity against colorectal cancer cells. X-ray and Fourier-transform infrared spectroscopy demonstrated that acid hydrolysis successfully degraded the amorphous cellulose to liberate the crystal regions. From transmission electron microscopy, CNC/5FU appeared as rod-like nanocrystals with an average length and width of 69.53 ± 1.14 nm and 8.13 ± 0.72 nm, respectively. The anticancer drug 5FU showed improved thermal stability after being loading onto CNC. From UV–vis spectroscopy data, the drug encapsulation efficiency in CNC/5FU was estimated to be 83.50 ± 1.52%. The drug release of CNC/5FU was higher at pH 7.4 compared to those at pH 4.2 and 1.2. From the cytotoxicity assays, CNC did not affect the viability of CCD112 colon normal cells. On the other hand, CNC/5FU exhibited anticancer effects against HCT116 and HT-29 colorectal cancer cells. The anticancer actions of CNC/5FU against HCT116 cells were then confirmed using an in vitro tumor-on-chip model and clonogenic assay. Mechanistic studies demonstrated that CNC/5FU killed the cancer cells by mainly inducing cell apoptosis and mitochondrial membrane damage. Overall, this study indicated that CNC/5FU could be a potential nanoformulation for improved drug delivery and colorectal cancer treatment.